Mind and nature - "Bateson, Gregory" (Fontana, 1980)
There are a number of books which I have never read but have seen cited literally hundreds of times, and foremost among them is Gregory Bateson's Steps to an Ecology of Mind. Following a friend's advice, however, I decided to start reading Bateson with Mind and Nature. A first glance at the paperback edition was not encouraging $1 (Bits classification by Bantam as a "New Age Book" was a bit disconcerting, and the blurb stressed the "interconnectedness of all things" line to the exclusion of anything else $1 (Bbut my fears proved unfounded. Mind and Nature is a introduction to epistemology (the study of knowledge) written by someone with a deep understanding of and respect for both the natural and social sciences.s
Keywords: "Knowledge, Theory."